A developmental model of an agricultural system in Thailand with particular reference to rice - Apichart Chirattiyangkur; Cowell, P. A.; Woo, Wai-Ling; Wadhwa, Lal Chand; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1974)
This study is an attempt to develop a model for investigating an agricultural system in Thailand with particular emphasis on the rice sector. Thailand. Rice is chosen as being a most important commodity in The study starts with examining and describing the agricultural system which is composed of the agricultural production function, marketing, consumption. This study is a theoretical approach. Since this is a first attempt to analyze the system in such a way it is recognized that the work described may only be regarded as preliminary, in which the major interrelating factors are illustrated. The model goes some way towards identifying the requirements for further research from which a more comprehensive model could be developed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1974
Keywords: Rice; Agriculture -- Thailand